The Future of Religious Moderation: A Study on The Opportunities and Challenges for the Existence of Religious Moderation Values in the Digital Age - Budi Santosa; Oksiana Jatiningsih; Maya Mustika Kartika Sari; Warsono; Iman Pasu Marganda Hardianto Purba; Rahmanu Wijaya; Sarmini (Indonesian Journal of Science, Technology and Humanities, 2024)
This research aims to look at the future of religious moderation, by examining the opportunities and challenges of the existence of religious moderation values in the digital era. By studying the opportunities and challenges of the existence of religious moderation values developed in the digital era, this research is expected to be able to provide a picture of the future in question. This research uses a qualitative approach with a library research method, exploring and reviewing various relevant literature materials in the form of research results based on scientific journals, e-books, magazines, phenomenon facts, news published in various information media channels such as online/offline newspapers, and various related sources that can help explain the future of the existence of religious moderation values in the digital era in the future. The results of this study show that the future of religious moderation in the digital era faces complex opportunities and challenges. On the one hand, digital technology opens up wide access to moderate religious sources, facilitates the spread of tolerance messages, and supports the improvement of religious literacy. On the other hand, challenges such as the spread of hoaxes, online radicalisation, polarisation of views, and limited digital literacy pose a serious threat to the sustainability of the development of religious moderation values